2023
DOI: 10.7759/cureus.33260
|View full text |Cite
|
Sign up to set email alerts
|

Awareness About Total Knee Arthroplasty Among Hail Population

Abstract: Background: Knee joint osteoarthritis is the most common among older adults. The knee joint needs to be treated surgically. The prevalence of this disorder is believed to be higher than 40% among people over 60. Objective: To study public awareness about total knee replacement among the Hail population and to explore the relationship between the level of awareness and different socio-demographic factors. Methods: A cross-sectional study was carried out in Hail, Saudi Arabia, using an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The high awareness levels regarding obesity as a risk factor align with studies conducted in different regions, emphasizing the universality of this perception [ 14 ]. However, gender-specific and age-related variations identified in this study contribute nuanced insights that may guide the tailoring of health education programs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high awareness levels regarding obesity as a risk factor align with studies conducted in different regions, emphasizing the universality of this perception [ 14 ]. However, gender-specific and age-related variations identified in this study contribute nuanced insights that may guide the tailoring of health education programs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of gender-based differences, health campaigns could employ diverse communication channels and content strategies to ensure equitable access and impact. Incorporating sociocultural considerations may enhance the effectiveness of interventions in promoting a holistic understanding of knee OA [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kwoh et al also supported these findings, highlighting the link between knowledge of total knee replacement and the willingness to undergo total knee arthroplasty [ 11 ]. However, a study by Alshammari et al [ 16 ] identified education as the sole predictor of awareness, with no significant variation in awareness scores related to gender, nationality, residence, or a history of chronic diseases. Our study similarly revealed that gender, marital status, knowledge about the prevalence of total knee arthroplasty in Saudi Arabia, and the belief that total knee arthroplasty is more common in males than females were not significantly associated with knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…The AI model gave accurate responses but showed limitations in personalization and regional specificity. It is a valuable resource for initial information and could help in remote areas, although it should not replace professional medical advice [68].…”
Section: Health Carementioning
confidence: 99%